PENERAPAN BIAYA KUALITAS UNTUK MENINGKATKAN EFISIENSI BIAYA PRODUKSI PADA CV. ULUNG BAURENO - Nurrofiah Nurrofiah; Yahya Yahya; Hartono Hartono (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2020)
In the current era of globalization of the world economy, company management competes with each other. Quality is one of the main factors that must be considered by companies so that they can survive in the midst of competitive competition. The author conducted this research in a cigarette company, CV. Ulung Baureno Bojonegoro. The variables in this study are quality costs as independent variables (X) and production cost efficiency as the dependent variable (Y). The research approach used is an explanatory research approach and the method used by the author is a quantitative descriptive method. The results of the research on total quality costs in 2018 recognized by the company amounted to Rp. 408.367.000 with a percentage of 3.96%. From the results of estimates obtained by lowering costs in the category of prevention costs, quality costs decreased by Rp 233.117.000 or equal to 2.26% of the actual sales total. So that it can be concluded that by applying quality costs can increase the efficiency of production costs.